Darius' Expedition against the Sakā Tigraxaudā - Harmatta, J.
ersch. 1979; = in: J. Harmatta (Ed.), Studies in the Sources on the History of Pre-Islamic Central Asia (Budapest 1979, Akadémiai Kiadó) 19-28.